Answer:
= 2
= k(k+1)
= (k+1)(k+2)
Step-by-step explanation:
We are given the statement,
as 2 + 4 + 6 + . . . + 2n = n(n+1)
That is,
as 2 + 4 + 6 + . . . + 2n = ![\sum_{i=1}^{n}2i](https://tex.z-dn.net/?f=%5Csum_%7Bi%3D1%7D%5E%7Bn%7D2i)
So, we have,
=
= 2
=
= 2 + 4 + 6 + . . . + 2k = k(k+1)
=
= 2 + 4 + 6 + . . . + 2k + 2(k+1) = (k+1)(k+2)
Thus, we get,
= 2
= k(k+1)
= (k+1)(k+2)
Answer:
3/5
Step-by-step explanation:
1/10+1/20=3/5
Answer:
4+9= 13
Step-by-step explanation:
Answer:
5x+y=17
Step-by-step explanation:
you subtract when you see the sign u add when u need to add.